The Role of Disturbed Mg Homeostasis in Chronic Kidney Disease Comorbidities - Rodelo-Haad, Cristian; Pendón-Ruiz de Mier, M. Victoria; Díaz-Tocados, Juan Miguel; Martin-Malo, Alejandro; Santamaria, Rafael; Muñoz-Castañeda, Juan Rafael; Rodríguez, Mariano (Frontiers in Cell and Developmental Biology, 2020)
Some of the critical mechanisms that mediate chronic kidney disease (CKD) progression are associated with vascular calcifications, disbalance of mineral metabolism, increased oxidative and metabolic stress, inflammation, coagulation abnormalities, endothelial dysfunction, or accumulation of uremic toxins. Also, it is widely accepted that pathologies with a strong influence in CKD progression are diabetes, hypertension, and cardiovascular disease (CVD). A disbalance in magnesium (Mg) homeostasis, more specifically hypomagnesemia, is associated with the development and progression of the comorbidities mentioned above, and some mechanisms might explain why low serum Mg is associated with negative clinical outcomes such as major adverse cardiovascular and renal events. Furthermore, it is likely that hypomagnesemia causes the release of inflammatory cytokines and C-reactive protein and promotes insulin resistance. Animal models have shown that Mg supplementation reverses vascular calcifications; thus, clinicians have focused on the potential benefits that Mg supplementation may have in humans. Recent evidence suggests that Mg reduces coronary artery calcifications and facilitates peripheral vasodilation. Mg may reduce vascular calcification by direct inhibition of the Wnt/β-catenin signaling pathway. Furthermore, Mg deficiency worsens kidney injury induced by an increased tubular load of phosphate. One important consequence of excessive tubular load of phosphate is the reduction of renal tubule expression of α-Klotho in moderate CKD. Low Mg levels worsen the reduction of Klotho induced by the tubular load of phosphate. Evidence to support clinical translation is yet insufficient, and more clinical studies are required to claim enough evidence for decision-making in daily practice. Meanwhile, it seems reasonable to prevent and treat Mg deficiency. This review aims to summarize the current understanding of Mg homeostasis, the potential mechanisms that may mediate the effect of Mg deficiency on CKD progression, CVD, and mortality.